MENINGKATKAN KEMAMPUAN PEMERINTAH DAERAH DALAM TATA KELOLA LAYANAN PUBLIK MELALUI PEMANFAATAN MODAL SOSIAL - Karoline RS Wenggi (GoAcademica Research dan Publishing, 2020)
Over the last few decades governance has moved towards decentralization. Local governments are given broader authority in regulating their own regions. However, each region varies widely in their capacity to implement governance. For this reason, it is necessary to increase the capacity of each region in carrying out governance. This form of ability can be done by utilizing the social capital that the area has. Thus this study aims to discuss local capacities in public administration governance through the use of social capital highlighting ways in which local governments can contribute positively to social capital formation by opening up their political opportunity structures and engaging non-profit organizations and community groups in partnership-based arrangements trust. This research is a qualitative research using literature review method in analyzing the object under study.